Approaching Vehicle Identification for the Visually Challenged - John Wiselin, M. C.; Aravind, C. V.; Rajparthiban, R.; Kumar, Uthaya (Asian Journal of Electrical Sciences, 2013)
The paper presents the development of a novel information system for the visually impaired. The objective of the developed system is to enable the visually impaired people to get information of the incoming source of vehicle without any other physical help and to travel by vehicle such as buses to their desired destinations. This device works in such a way, where the visually impaired people are able to detect the arrival of a particular vehicle as their only source of transportation. The system incorporated is designed to be simple and portable hand held for the convenient usage. A simple wireless communication system with frequency modulation is employed for the signal transmission. The microcontroller in the system is used to generate the automatic signal that is transmitted through the FM transmitter. The signal picked up by a single chip FM receiver and announces voice message of the coming vehicle information using the voice record and playback device. In this way the visually impaired will manage to catch the vehicle by their own ability. However the model developed aims for identify only one vehicle but can be extended to any number of systems. The FM carrier frequency used for communication between the transmitter and receiver is 89.3MHz. The maximum transmission distance for transceivers signal is roughly about 0.5 to 1 meter.